1990
DOI: 10.1159/000177573
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cortisol and Adrenal Ascorbic Acid Levels after ACTH Treatment with a High Intake of Ascorbic Acid in the Guinea Pig

Abstract: The influence of ascorbic acid (AA) intake on plasma cortisol (PC) and tissue AA levels after ACTH treatment was examined using guinea pigs. ACTH produced an 8- to 10-fold rise in PC levels (p < 0.0001) over the 4-hour experimental period compared to gel-injected control animals. The magnitude of rise in PC was similar at both normal (0.50 g/kg diet) and high (10 g/kg diet) AA intakes. A 30–100% higher (p < 0.0001) level of AA in tissues (adrenals, liver, and kidneys) and plasma was observed with the high AA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Last, similarly to earlier findings (60), ACTH treatment did not influence plasma ascorbic acid concentrations. Taken together these data indicate that the absolute concentration of ascorbic acid within the adrenal gland is not critical for the synthesis of cortisol (63). While ascorbic acid is required for the synthesis of cortisol, ascorbic acid does not appear to be released simultaneously with cortisol as a stress response.…”
Section: Ascorbic Acid and Cortisolmentioning
confidence: 73%
See 1 more Smart Citation
“…Last, similarly to earlier findings (60), ACTH treatment did not influence plasma ascorbic acid concentrations. Taken together these data indicate that the absolute concentration of ascorbic acid within the adrenal gland is not critical for the synthesis of cortisol (63). While ascorbic acid is required for the synthesis of cortisol, ascorbic acid does not appear to be released simultaneously with cortisol as a stress response.…”
Section: Ascorbic Acid and Cortisolmentioning
confidence: 73%
“…In another study by the same group, the vitamin C content of diets fed to guinea pigs was manipulated, injections of ACTH were administered to the animals, and the resultant alterations in adrenal ascorbic acid and plasma cortisol concentrations were measured (63). Although dietary vitamin C strongly influenced the concentration of ascorbic acid in the adrenal glands, it was without effect on basal or ACTH-stimulated changes in plasma cortisol.…”
Section: Ascorbic Acid and Cortisolmentioning
confidence: 99%
“…Few studies have investigated the influence of vitamin C on immune responses following intense endurance exercise. Vitamin C is highly concentrated in the adrenal cortex, and it has been hypothesized that vitamin C supplements may influence serum cortisol release and alterations in immune function following heavy exertion (Enwonwu et al 1995;Kodama et al 1994;Laney et al 1990;Redmann et al1995). In some animal models, vitamin C depletion has been associated with a significant increase in serum cortisol without an increase in adrenocorticotrophic hormone (ACTH) (Enwonwu et al 1995;Redmann et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Yanagibashi et al [15] found in bovine glomerulosa cells, that ascorbate and NADPH provides operative risk from etomidate induced adrenocortical suppression has to be discussed with caution, as corti-reductive equivalents that only support the last step in aldosterone synthesis. Laney et al [16] examined sol depletion is incomplete. the influence of ascorbic acid intake on plasma cortisol and tissue ascorbate levels after ACTH treatment in guinea pigs.…”
Section: Resultsmentioning
confidence: 99%